Trypsin inhibitor LH011 inhibited DSS-induced mice colitis via alleviating inflammation and oxidative stress - Jia, Zhenmao; Wang, Panxia; Xu, Yuansheng; Feng, Guodong; Wang, Quan; He, Xiangjun; Song, Yan; Liu, Peiqing; Chen, Jianwen (Frontiers in Pharmacology, 2022)
Background: Ulcerative colitis (UC) is one type of inflammatory bowel diseases, characterized by inflammation for the infiltration and activation of macrophages in colonic tissue. LH011 a trypsin inhibitor with potential anti-inflammatory effect. Purpose: Here, we aim to assay the effects of LH011 on UC and further explore underlying mechanisms in vitro and in vivo. Methods: Dextran sulfate sodium (DSS, 3.5 %) was used to induce UC and lipopolysaccharide (LPS) was used to induce inflammation in RAW 264.7 cells. LH011 was administrated to mice in vivo or RAW264.7 cells in vitro at different concentrations. The cytokines (IL-1β, IL-6 and TNF-α) and the changes of NF-κB and Nrf2 pathways were detected. Results: We found that LH011 attenuated weight loss, disease activity index (DAI) and colonic pathological damage in DSS-induced mice colitis. Additionally, LH011 inhibited the expression of IL-1β, IL-6 and TNF-α and strengthened the antioxidant capacity. Mechanically, LH011 down-regulated the nuclear localization of NF-κB p65 and up-regulated the expressions of Nrf2 proteins expressions. Conclusions: These results demonstrated that LH011 alleviated inflammation and oxidative stress during UC by inhibiting TLR4/NF-κB and activating Nrf2/Keap1/HO-1 signaling pathways.